PERANCANGAN SISTEM INFORMASI WEBSITE MULTIUSER MENGGUNAKAN PHP-HTML DAN PENGOLAHAN DATA MENGGUNAKAN GOOGLE DATA STUDIO DI BKB NURUL FIKRI - Muhamad Rio Ramdani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Along with the rapid development of the internet today which is very influential on human life, the internet makes it easier for us to access important information that can be done anywhere and anytime, not depending on location or time. Thus this can be utilized by a company in terms of dissemination and receipt of information via the internet. Therefore, this research will develop an online-based data processing website, so that it can support the process of distributing and receiving information containing company data. The method used in this design is Observation, which is collecting data through direct observation. The programming language uses PHP-HTML while the database uses MySQL / XAMPP. With the creation of an online-based website, it is hoped that it will make it easier for users to analyze data and make decisions based on existing data